Analysis of Sports Facility Service Quality on Goro Consumer Satisfaction Arena Makassar - Muhammad Hanif Muhtadi; Ramli Ramli; Herman Herman; Muh. Adnan Hudain; Irvan Irvan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research is a quantitative descriptive study that aims to clarify customer satisfaction at Goro Arena. The population in this study was 145 members registered at Goro Arena. Sampling technique with the accidental sampling method. The sample was 22 members who were doing sports activities at the Goro Arena. The instrument used to understand customer satisfaction is a questionnaire. The data analysis technique uses using quantitative descriptive analysis method with percentages. Based on the research analysis, the quality of sports facility services on customer satisfaction at the Makassar Goro Arena is very satisfactory with a percentage of 57%. According to Parasuraman in Jayanti (2016), the form of service quality application uses the concept of "RATER" which stands for Responsiveness, Assurance, Tangibles, Empathy, and Reliability. Viewed through the aspects of service satisfaction of the Goro Arena facility, the following data were obtained: the responsiveness factor (responsiveness) was included in the very satisfied group by 70%; the assurance factor (assurance) was included in the very satisfied group by 50%; the tangibles factor was included in the satisfied group by 53%; the empathy factor (empathy) was included in the very satisfied group by 60%; the reliability factor (reliability) was included in the very satisfied group by 50%. From these results, it can be seen that the quality of sports facility services to customer satisfaction in Goro Arena Makassar has a very satisfying category.